Studi Inventarisasi Hewan Invertebrata Di Pantai Monta Kabupaten Bima - Oktavianus Sarno; Ayu Rahmawati; Nurul Fahida; Winarti; Sukarni (Jompa Research and Development, 2024)
Field practicum held by students of Gnggusuwaru University, Biology Education Study Program, on Sarae Me'e Beach with the aim of clarifying invertebrate animals. There are several animal phyla that we found, namely the cnidaria phylum and the echinoderm phylum, which live on rocks at a distance of 3.95 meters from sea water. The arthropod phylum lives in sea water at a depth of 1.5 meters from the sea surface. The mollusk phylum lives on land at a distance of 15 meters from sea water.